DESCRIPTION OF CLINICAL POLYPHARMACY PRESCRIPTIONS IN TYPE 2 DIABETES MELLITUS PATIENTS AT HOSPITAL X JEMBER DISTRICT - Nurul Fathona; Shinta Mayasari; Nafisah Isnawati (LPPM Universitas dr. Soebandi, 2024)
Background: Diabetes mellitus (DM) is a metabolic disease caused by insulin resistance and pancreatic beta cell dysfunction. Polypharmacy is the use of three or more drugs every day is very common in patients with diabetes mellitus. WHO data shows that the prevalence of Diabetes Mellitus (DM) polypharmacy will reach 7.4% - 43.4% by 2023. Objective: This study aims to determine the clinical picture of polypharmacy prescriptions in patients with type 2 diabetes mellitus at X Hospital, Jember Regency. Method: This study used a descriptive non-experimental method by observation, involving 80 samples. Samples were selected by random sampling and data were analysed and displayed in the form of frequencies and percentages using Microsoft Excel and SPSS. Results: The results of this study are the description of the most polypharmacy prescriptions, namely prescriptions with 3 drug items as many as 3 prescriptions (7.5%), and the description of the least polypharmacy prescriptions, namely prescriptions with 4 drug items, and prescriptions with 10 drug items as many as 1 prescription (1%). In addition, the results of this study also contained drug interactions as many as 72 interacting prescriptions. Conclusion: From the discussion above, it can be concluded that, in the study at Hospital X, Jember Regency, polypharmacy was found from the samples analysed, all of which were polypharmacy prescriptions. This study also found that prescriptions for type 2 diabetes mellitus patients experienced drug interactions with moderate interactions being the most common. These interactions can reduce the effectiveness of treatment and increase risks for patients.